PENERAPAN SISTEM INFORMASI MANAJEMEN PENDIDIKAN TERHADAP MUTU LAYANAN AKADEMIK PADA SEKOLAH MENENGAH ATAS DI KABUPATEN BOGOR - Rohmah, Siti; Hasanah, Tita; Lestari, Hana (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2024)
This study aims to determine the effect of the education management information system on the quality of academic services in Senior High Schools. This type of research is quantitative with a survey method and using random sampling techniques. The location of the study was in Cibungbulang District, Bogor Regency. The research subjects were 104 respondents. The data analysis technique was inferential statistics with a simple regression test assisted by SPSS 19. The results showed that there was an influence between the education management information system on the quality of academic services with an R Square value = 0.172. So it can be interpreted that the education management information system variable has an influence on the quality of academic services by 17.2%. Therefore, to improve the education management information system, it is expected that each educational unit can improve the quality of its academic services.